The Relationship between Emotional Intelligence and Patients’ Demographic Characteristics referred to Iranshahr University of Medical Sciences hospitals in 2014 - Masoomeh Shahnavazi (Journal of Global Pharma Technology, 2017)
Background and objective the patients under hem dialysis treatment experience so much stress associated with care plans and limitations in social communication. Because of the significant role of emotional intelligence on improving mental health and the fact that there is no precise information of hem dialysis patients’ emotional quotient, the investigation of emotional intelligence in this context as well as designing and implementation of effective training programs can be regarded as a basis for enhancing this important variable. Method this is a descriptive-correlation study conducted in 2014 of the patients under hem dialysis treatment took part in the study according to the complete enumeration method and the required criteria. The data collection instruments included individual particulars and Cyberia-Shrink Emotional Intelligence questionnaire. The data were analyzed by using descriptive and analytical statistics (mean and standard deviation), analysis of variance (ANOVA), independent T-test, and Schaffer test through SPSS 16. Findings the mean and standard deviation of emotional intelligence total score were43.99±10.50. The results indicated that there is a statistically significant relationship between emotional intelligence and gender (p = 0.03), marital status (p = 0.02), smoking status (p = 0.001), and economic condition (p = 0.04) in different age groups (p = 0.03). There was also a statistically inverse relationship between emotional intelligence mean score and systolic and diastolic blood pressure (P = 0.001and P = 0.03, respectively). Furthermore, there was not a statistically significant relationship between emotional intelligence and the variables ‘weight, educational level, occupational status, and place of residence’. Conclusion with regard to the relationship between some demographic characteristics and emotional intelligence, designing and implementation of effective training programs can improve this crucial element in patients with chronic kidney disease and under hem dialysis treatment.Keywords: Emotional intelligence, Chronic kidney disease, Hem dialysis, Demographic characteristics.